1998
DOI: 10.1126/science.279.5353.1037
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of GABPα/β: An ETS Domain- Ankyrin Repeat Heterodimer Bound to DNA

Abstract: GA-binding protein (GABP) is a transcriptional regulator composed of two structurally dissimilar subunits. The alpha subunit contains a DNA-binding domain that is a member of the ETS family, whereas the beta subunit contains a series of ankyrin repeats. The crystal structure of a ternary complex containing a GABPalpha/beta ETS domain-ankyrin repeat heterodimer bound to DNA was determined at 2. 15 angstrom resolution. The structure shows how an ETS domain protein can recruit a partner protein using both the ETS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
232
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(256 citation statements)
references
References 26 publications
(13 reference statements)
19
232
1
1
Order By: Relevance
“…Therefore, GABPb or GABPg should bind GABPa in the cytoplasm to assist GABPa transport into the nucleus. [18][19][20] GABP is now also recognized as a key transcriptional regulator of dynamically regulated, lineage-restricted genes, especially in myeloid cells and at the neuromuscular junction, and acts as an integrator of the cellular signaling pathway by regulating key hormones and transmembrane receptors. 17 Recently, we found that the heteromeric complex of GABP (GABPa/b) acts as a transcriptional repressor and thereby inhibits VEGF expression in SH-SY5Y neuroblastoma and green monkey kidney epithelial (CV-1) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GABPb or GABPg should bind GABPa in the cytoplasm to assist GABPa transport into the nucleus. [18][19][20] GABP is now also recognized as a key transcriptional regulator of dynamically regulated, lineage-restricted genes, especially in myeloid cells and at the neuromuscular junction, and acts as an integrator of the cellular signaling pathway by regulating key hormones and transmembrane receptors. 17 Recently, we found that the heteromeric complex of GABP (GABPa/b) acts as a transcriptional repressor and thereby inhibits VEGF expression in SH-SY5Y neuroblastoma and green monkey kidney epithelial (CV-1) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the basis of NMR analyses of the secondary structures of tumor suppressor p16, we first reported that ankyrin-repeats consist of helix-turn-helix (H-T-H) motifs (13). Subsequently, the tertiary structures of several proteins containing ankyrin repeats have been reported: the crystal structures of 53BP2 (14), p18 (15), and transcriptional regulator GABPR/ bound to DNA (16) and the solution structures of p19 (17), p16 (18), and myotrophin (19). In all of these structures, ankyrin repeats exist as H-T-H motifs linked by loops.…”
mentioning
confidence: 99%
“…(b) In the crystal structure of the transcriptional regulator GABPR/ -DNA complex, the -subunit consists of 5 ankyrin repeats linked by 4 loops. The interface between R-and -subunits involves mainly the tips of the loops of the -subunit (16). The tip of one of the loops in 53BP2 is also involved in the binding to p53 (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA-binding component is the ␣ subunit (GABP␣) containing the conserved Ets domain, a winged helix-turn-helix protein motif (6). The ␤ subunit (GABP␤) is bound to GABP␣ via repeats of the Notch-ankyrin type (19).…”
mentioning
confidence: 99%